Loneliness and Self Control Predict Online Gaming Addiction Among Students: Kesepian dan Pengendalian Diri Memprediksi Kecanduan Bermain Game Online di Kalangan Mahasiswa - Abdul Rochman; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid technological advancement and widespread internet access have made online gaming a dominant leisure activity among university students, raising concerns about maladaptive gaming behaviors. Specific Background: Students are particularly vulnerable to excessive gaming due to developmental, social, and psychological factors that shape their daily routines and coping strategies. Knowledge Gap: Although prior studies have examined determinants of problematic gaming, empirical evidence simultaneously analyzing loneliness and self control as psychological predictors within a university population remains limited. Aims: This study investigated the relationship between loneliness and self control with tendencies toward online gaming addiction among undergraduate students. Results: Using a quantitative correlational design with multiple linear regression on 375 students who regularly played online games at least three hours daily for six months, the findings revealed a significant positive correlation between loneliness and gaming addiction (r = 0.269) and a significant negative correlation between self control and gaming addiction (r = −0.137). Novelty: The study provides integrated evidence that emotional isolation and behavioral regulation jointly relate to addictive gaming tendencies within a large student sample from an Indonesian university context. Implications: These findings suggest that interventions addressing social connectedness and strengthening self regulatory capacities may help reduce problematic online gaming behaviors among university students. Highlights: Higher perceived isolation corresponds with stronger compulsive play patterns. Stronger personal regulation capacity associates with lower problematic use. Most participants exhibited moderate levels across all measured variables. Keywords: Online Gaming Addiction; Loneliness; Self Control; University Students; Behavioral Regulation